Study on CD36 gene expression in megakaryocytic lineage derived from umbilical cord blood hematopoietic stem cells cultured in vitro - XU Fang; YU Guangshu; LING Xia; HE Ji; XU Xianguo (Zhongguo shuxue zazhi)
[Objective] To elucidate the expression level and transcript structure of the CD36 gene in megakaryocytes cultured in vitro. [Methods] Using umbilical cord blood CD34+ hematopoietic stem cells as the starting point, megakaryocytic lineage cells were directionally cultured in vitro using different combinations of cytokines. Total cell RNA was extracted from cultures at 0 d, 7 d, and 12 d, and megakaryocyte RNA was extracted from CD41a-sorted cells after 14 d and 18 d of culture. RNA-NGS sequencing technology was used to analyze the RNA gene expression profiles across the five culture periods and further investigate CD36 gene expression. [Results] The number of megakaryocytes generated in the TPO (100 ng/mL) group [(2.2±0.02)×106/mL] was significantly higher than that in the other five groups. A total of 22 066 expressed genes were detected in the RNA of the five culture periods, and gene expression levels at each time point were correlated with the culture timeline. CD36 gene expression increased with culture time, with FPKM values for CD36 expression in the megakaryocytic lineage at 14 d and 18 d being 18.35 and 101.85, respectively, which were much lower than those for ITGA2B and ITGB3 genes but slightly higher than that for CD109 gene in the megakaryocytic lineage. The longest transcript of CD36 in the 18 d megakaryocytic lineage was 3.8 kb, encompassing all sequence of exons E3 to E14 and a partial sequence of E15. [Conclusion] This is the first report on the expression level and transcript structure of the CD36 gene in megakaryocytes cultured in vitro, providing fundamental data for research on the expression and regulation of the CD36 gene in the megakaryocytic lineage.